AN INVESTIGATION INTO MOBILE-ASSISTED LANGUAGE LEARNING: FROM THEORY TO APPLICATION - Duysenbaeva Shaxnoza Kadirbaevna (World Scientific Research Journal, 2025)
Abstract: Mobile devices have quickly taken over language learners' lives, providing them with previously unheard-of access to reading resources and chances for individualized instruction. While the potential of mobile-assisted language learning (MALL) is widely accepted, the specific nuances of how mobile devices uniquely influence reading skill development require closer scrutiny. This article defines the peculiarities of using technology to enhance learners reading skills, focusing on the interplay between device affordances (e.g., portability, interactivity, multimodal capabilities), cognitive processes (e.g., attention, working memory, motivation), and pedagogical methods. We will look through and analyze existing research drawing upon frameworks from cognitive load theory, constructivism, and multiliteracies to explore the specific merits and complexities of mobile reading. Ultimately, this article endeavors to provide a nuanced comprehension of how to effectively leverage mobile technologies to cultivate engaged and proficient readers.